IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI PELALAWAN NOMOR 12 TAHUN 2012 TENTANG PEMBINAAN DAN PENEGAKAN DISIPLIN PEGAWAI - Pramudya, Agung; Heriyanto, Meyzi; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Policy Implementation of Regulation of Pelalawan Regent Number 12 Year 2012 About Fostering and Enforcing Employee Discipline. This study aims to determine the implementation of the policy Pelupawan Puppet No. 12 of 2012. This type of research is qualitative. The research informants were taken by purposive sampling consisting of Secretary of Service, Head of Sub Division of General and Personnel, Treasurer, 10 employees of Local Revenue Office of Pelalawan Regency and society. Data collection techniques are interviews and observations. Data analysis techniques use interactive models ranging from data reduction, data testing and conclusion. The result of the research shows that the standard factor and the target of the policy made have not been well executed by the employee as the implementing agent of the policy. This can be seen from the many violations of discipline that occurred.